A survey of the manpower resources of Curuan community and its implications for the Curuan Barrio High School organization and curriculum - Villares, Roberto 1921- (s.n.], 1972)
The manpower resources of the barrio of Curuan was examined. On the basis of its findings, implications were drawn for the organization structure and the curriculum of Curuan Barrio High School.